Dog years - Yancy, Melissa (Pitt drue heinz lit prize, 2016)
"Many of these richly layered stories juxtapose the miracles of modern medicine against the inescapable frustrations of everyday life: awkward first dates, the indignities of air travel, and overwhelming megastore cereal aisles. In "Go Forth," an aging couple attends a kidney transplant reunion, where donors and recipients collide with unexpected results; in "Hounds," a woman who runs a facial reconstruction program for veterans nurses her dying dog while recounting the ways she has used sex as both a weapon and a salve; and in "Consider This Case," a lonely fetal surgeon caring for his aesthete father must reconsider sexuality and the lengths people will go to have children. Melissa Yancy's personal experience in the milieus of hospitals, medicine, and family services infuse her narratives with a rare texture and gravity. Keenly observant, offering both sharp humor and humanity, these stories explore the ties that bind--both genetic and otherwise--and the fine line between the mundane and the maudlin. Whether the men or women that populate these pages are contending with illness, death, or parenthood, the real focus is on time and our inability to slow its progression, reminding us to revel in those moments we can control"--